ANALISIS DAYA SAING KOPI INDONESIA DI PASAR ASEAN PASKA SETAHUN PEMBERLAKUAN MASYARAKAT EKONOMI ASEAN - Robby A. Sirait; Rendy Alvaro (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2017)
The analysis of the competitiveness of Indonesian coffee aims to convey Indonesian's coffee export position amidst the ASEAN trades, particularly after one year of the establsihment of ASEAN Economic Community. The research used three economic indicators in order to measure the competitiveness of Indonesian coffee. These indicators are RCA (Revealed Comparative Advantage), EPD (Export Product Dynamics), and MS (Market Share). The three indicators were used in period of 2011 and 2016 in the ASEAN market. The results showed that the coffee product with HS-090111 code possesses predominant export and high potential quality. Meanwhile, the coffee product with HS-090121 code has a significant growth as well as high level competitiveness within the ASEAN market. For that reasons, government policy to support Indonesian coffee is a must.